2018
DOI: 10.1080/15384047.2018.1537579
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG5 affects cell proliferation, metastasis and migration of colorectal cancer through regulating miR-132-3p/CREB5

Abstract: We aimed at the effects of long non-coding RNA (lncRNA) SNHG5 on proliferation, metastasis and migration of colorectal cancer (CRC) cells. We also investigated regulatory relationships among miR-132-3p, SNHG5 and CREB5 and their roles in CRC. 25 pairs of samples containing CRC tissues and matched para-tumor tissues were obtained to examine SNHG5, miR-132-3p and CREB5 expression by qRT-PCR or Western blot. The targeted relationship between miR-132-3p and SNHG5 or CREB5 was confirmed by dual luciferase report as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 25 publications
4
57
0
Order By: Relevance
“…Many studies have demonstrated that lncRNAs function as miRNA sponges to participate in tumorigenesis. LncRNA-SNHG5 has been found to promote the development of colorectal cancer by sponging miR-132-3p/ CREB5 [18]. In our research, lncRNA-SNHG5 was confirmed as a molecular sponge of miR-1179.…”
Section: Discussionsupporting
confidence: 63%
“…Many studies have demonstrated that lncRNAs function as miRNA sponges to participate in tumorigenesis. LncRNA-SNHG5 has been found to promote the development of colorectal cancer by sponging miR-132-3p/ CREB5 [18]. In our research, lncRNA-SNHG5 was confirmed as a molecular sponge of miR-1179.…”
Section: Discussionsupporting
confidence: 63%
“…Additionally, recent studies showed that the abnormal expressions of miR-125a and CREB5 were involved in the development of CRC [17,22,35]. Thus, in this manuscript, we further explored whether circVAPA silencing could exert the anti-tumor effect in CRC cells through modulating miR-125a/CREB5 axis.…”
Section: Discussionmentioning
confidence: 93%
“…In epithelial ovarian cancer, CREB5 facilitated cell invasion and suggested a poor prognosis [21]. Moreover, relevant literature exhibited that CREB5 could work as the tumor-promoting effect through expediting proliferation, metastasis, migration and hampering apoptosis in CRC [22].…”
mentioning
confidence: 99%
“…The pathogenesis and carcinogenic mechanisms of CRC are multifactorial and complex processes involving different genetic and epigenetic changes. LncRNA has been found to play an important role in the occurrence and development of CRC, including: APC 49,50 , OCC-1 33 , FEZF1-AS1 47,51 , SNHG5 52,53 and so on.…”
Section: Discussionmentioning
confidence: 99%